Identifying the neuropsychiatric health effects of low-dose lithium interventions: A systematic review. (January 2023) - Strawbridge, Rebecca; Kerr-Gaffney, Jess; Bessa, Giulia; Loschi, Giulia; Freitas, Hanna Luísa O.; Pires, Hugo; Cousins, David A.; Juruena, Mario F.; Young, Allan H.
Abstract: Background: Lithium is widely evidenced for its neuropsychiatric benefits. Advantages of 'sub-therapeutic' doses are increasingly being reported, which is apposite given enduring concerns around adverse effects of 'therapeutic' doses. We aimed to synthesise all available evidence from interventional studies investigating low-dose lithium (LDL) across neuropsychiatric outcomes. Methods: Electronic databases were systematically searched to include studies where a group of adult humans were treated with LDL (∼serum level ≤0.6 mmol/L), where data describing a neuropsychiatric outcome were reported either before and after treatment, and/or between lithium and a comparator. Results: 18 articles were examined and grouped according to outcome domain (cognition, depression, mania, and related constructs e.g., suicidality). Significant benefits (versus placebo) were identified for attenuating cognitive decline, and potentially as an adjunctive therapy for people with depression/mania. Across studies, LDL was reported to be safe. Conclusions: Despite the paucity and heterogeneity of studies, LDL's apparent pro-cognitive effects and positive safety profile open promising avenues in the fields of neurodegeneration, and augmentation in affective disorders. We urge future examinations of LDL's potential to prevent cognitive/affective syndromes. Highlights: Lithium is effective for a plethora of indications, but high doses confer adverse effects. 'Sub-therapeutic' doses have potential benefits but these have not been reviewed. We sought all studies reporting low dose lithium's effects on neuropsychiatric health. Low-dose lithium is safe, and may improve cognition, as well as affective symptoms as an augmenter. Evidence is scant but suggests promise for low-dose lithium to improve various neuropsychiatric outcomes.